Learner's belief on their English oral acquisition through role-play activities: a case study of part 2 diploma students of Universiti Teknologi Mara (UiTM) Segamat / Mohd Izuan Ismail - Ismail, Mohd Izuan (2011)
This study is intended to investigate the beliefs and perceptions of Part 2 diploma students of Universiti Teknologi MARA (UiTM) Segamat towards their oral English acquisition through the five proposed roleplay activities: Drama, Project Runway, The Discussion, The Business and Show & Tell. The objective of the study is to find out the relationship between the Beliefs About Language Learning Inventory (BALLI) items and students’ beliefs in the English language, the perceptions of these respondents towards role-play activities, which of these role-play activities is the most interesting for them to use English and whether these role-play activities can change their perception towards the English language. To accomplish this study, sixty questionnaires were distributed to the respondents from the three classes: D2C1, D2T1 and D2T2. Through the questionnaires, the researcher attempted to answer five research questions. From the data gathered, the findings of the research proved that there is a positive relationship between BALLI and respondents’ belief. In addition, the findings also showed that the most interesting role-play activity for respondent is Project Runway. Furthermore, the findings also revealed respondents’ thoughts about the issue and their opinion on how to improve role-play activities.